Common genetic variants associated with disease from genome‐wide association studies are mutually exclusive in prostate cancer and rheumatoid arthritis. (18th September 2012) - Orozco, Gisela; Goh, Chee L.; Al Olama, Ali Amin; Benlloch‐Garcia, Sara; Govindasami, Koveela; Guy, Michelle; Muir, Kenneth R.; Giles, Graham G.; Severi, Gianluca; Neal, David E.; Hamdy, Freddie C.; Donovan, Jenny L.; et al.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? The link between inflammation and cancer has long been reported and inflammation is thought to play a role in the pathogenesis of many cancers, including prostate cancer (PrCa). Over the last 5 years, genome‐wide association studies (GWAS) have reported numerous susceptibility loci that predispose individuals to many different traits. The present study aims to ascertain if there are common genetic risk profiles that might predispose individuals to both PrCa and the autoimmune inflammatory condition, rheumatoid arthritis. These results could have potential public heath impact in terms of screening and chemoprevention. Objectives To investigate if potential common pathways exist for the pathogenesis of autoimmune disease and prostate cancer (PrCa). To ascertain if the single nucleotide polymorphisms (SNPs) reported by genome‐wide association studies (GWAS) as being associated with susceptibility to PrCa are also associated with susceptibility to the autoimmune disease rheumatoid arthritis (RA). Materials and Methods The original Wellcome Trust Case Control Consortium (WTCCC) UK RA GWAS study was expanded to include a total of 3221 cases and 5272 controls. In all, 37 germline autosomal SNPs at genome‐wide significance associated with PrCa risk were identified from a UK/Australian PrCa GWAS. Allele frequencies were compared for these 37 SNPs between RA cases and controls using a chi‐squared trend test and corrected for multiple testing (Bonferroni). Results In all, 33 SNPs were able to be analysed in the RA dataset. Proxies could not be located for the SNPs in 3q26, 5p15 and for two SNPs in 17q12. After applying a Bonferroni correction for the number of SNPs tested, the SNP mapping to CCHCR1 (rs130067) retained statistically significant evidence for association (P = 6 × 10–4; odds ratio [OR] = 1.15, 95% CI: 1.06–1.24); this has also been associated with psoriasis. However, further analyses showed that the association of this allele was due to confounding by RA‐associated HLA‐DRB1 alleles. Conclusions There is currently no evidence that SNPs associated with PrCa at genome‐wide significance are associated with the development of RA. Studies like this are important in determining if common genetic risk profiles might predispose individuals to many diseases, which could have implications for public health in terms of screening and chemoprevention.